( n → 0 + lim x → 0 + lim x n ) − ( x → 0 + lim n → 0 + lim x n ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
[This is not a solution]
The reason why the answer is not 0, is because we cannot simply interchange the order of limits, even though these functions are continuous. That is because, the pointwise limit of the functions is not continuous, resulting in this difference. In particular, n → 0 + lim x n = { 1 0 0 < x ≤ 1 x = 0
This begins to delve into the area of analysis (much more rigourous calculus), which deals with continuity and convergence.
Well, you did not really simply change the order of the limits . You added a + too!
By the way, the inspiration problem does not redirect to Anandhu Raj's problem
Log in to reply
Thanks, they were all supposed to have a +, to avoid dealing with negative/complex exponents. (fixed)
The inspiration was from a comment in a solution. Sometimes, the link to a solution comment doesn't work well, because you first land on the problem. I have made this more explicit. Thanks!
Problem Loading...
Note Loading...
Set Loading...
the first limit = 0 because as x → 0, x n = 0 regardless of n , but the second limit = 1 because as n → 0, x n = 1 regardless of x as both never actually reach zero. [This is not intended to be the most rigorous solution]